Diversity of questing ticks and prevalence of tick-associated pathogens in Khao Kheow-Khao Chomphu Wildlife Sanctuary, Chon Buri, Thailand - Wittawat Wechtaisong; Chalida Sri-in; Kritsada Thongmeesee; Elizabeth Riana; Thuong Thi Huyen Bui; Lyric C. Bartholomay; Sonthaya Tiawsirisup (Current Research in Parasitology and Vector-Borne Diseases)
Ixodid ticks are important vectors for tick-borne diseases distributed worldwide, including Thailand. Recreation areas within wildlife habitats are considered high-risk zones for tick exposure and tick-borne disease in humans. The study aimed to determine seasonal variations in tick diversity and pathogen prevalence in Khao Kheow-Khao Chomphu Wildlife Sanctuary, Chon Buri, Thailand. From November 2021 to March 2023, a total of 1331 immature ticks were collected by dragging. The proportion of collected larvae was highest in February 2022, while the number of collected nymphs peaked in December 2021. Seven tick species were molecularly identified: Haemaphysalis lagrangei, H. wellingtoni, H. shimoga, H. obesa, Dermacentor auratus, Rhipicephalus microplus, and Amblyomma integrum. Of 80 tick pools, Anaplasma, piroplasms (Babesia and Theileria), Bartonella, and Rickettsia were detected in 10% (8/80), 3.75% (3/80), 1.25% (1/80), and 3.75% (3/80) of tick pools, respectively. Phylogenetic analysis grouped the newly generated sequences in the clades of Anaplasma bovis, Babesia gibsoni, Theileria cervi, Bartonella henselae, and Rickettsia montanensis. A seasonal pattern of pathogen appearance was detected during November to February, the cool season in Thailand. Based on our results indicating the highest peak of immature ticks and prevalence of pathogens, visitors should take precautions to avoid tick exposure during this season.